When the confidential becomes public: access to documents of repression in the custody of public archives - Moraes, Maria Blassioli [UNESP]; Bizello, Maria Leandra [UNESP] (Univ Brasilia, Dept Ciencia Informacao, 2022)
The article analyzes how the state and national archives are structuring and enabling a distance research in their holdings. Therefore, an investigation was carried out on the possibilities of researching the archives obtained by repressive agencies of the military dictatorship, in Brazil (1964-1985), and which are held in the custody of public archives. The documents of bodies such as the National Information Service, at the federal level, and those of the Departments of Political and Social Order, the state bodies linked to the Secretariats of Public Security, were transferred from the 1990s to the custody of files public, which allowed the opening to the public. The methodology adopted was based on a bibliographic survey and qualitative analysis of the sites of the state archives that contain the documents of the political police and the National Archive, which in addition to guarding the documents of the National Information Service, developed by the Revealed Memories Project, through which the documents of the law enforcement agencies were reproduced and subsequently made available on a website on the internet. We analyzed the archive sites, the existence of access rules, description rules, finding aids and documents scanned and made available to the user. An investigation made it possible to realize that some institutions not explored on the internet site, but that others that have it, make the finding aids and access rules available without, however, granting the digitized documents. Few institutions available on the websites, access and possibility of capturing documents. It is noticed the existence of finding aids according to international and national description standards, however, while there is alignment in relation to archival description, there are different standards of norms regarding access to these documents. It is concluded that there is a need to advance on archives access policies and that it is necessary to understand whether the exercise of control over the archives created is broadly accessible.
Keywords: Public archive; Access to information; Military dictatorship; Access policy